A Comparative study of log volume estimation by using statistical method - Syed Ahmad, Sharifah Sakinah; Mohd Mushar, Siti Hajar; Zamah Shari, Nur Hajar; Kasmin, Fauziah (EDUCATUM Journal of Science, Mathematics and Technology, 2020)
Log volume estimation is a measurement of the amount of merchantable volume and precise estimation of log volume plays an important role in sustainable forest management. There are several log volume formula which commonly used in estimating the log volume, however, there are significant differences between each formula. Therefore, this paper evaluates the performance of three different log volume formula which are Smalian’s, Huber’s and Bruce’s formula against several log sectional length. The performance of each log volume formula will be evaluated in terms of the bias, precision and accuracy of the estimation. The result shows that Huber’s formula performs the best for log sectional length of 2 m, 4 m, 6 m and 8 m log sectional length. The log sectional length and prediction accuracy is inversely related whereby the shorter the log sectional length, the better the prediction accuracy is.